Redesain Rancangan Ultimate Pit Dengan Menggunakan Software Minescape 4.118 Di Pit S41 PT. Energi Batu Hitam Kecamatan Muara Lawa & Siluq Ngurai, Kabupaten Kutai Barat, Kalimantan Timur - Devit Aswandi; Dedi Yulhendra (Journals Mining Engineering : Bina Tambang, 2019)
Abstract. The research was conducted at PT. Energi Batu Hitam in Muara Lawa and Siluq Ngurai, West Kutai, East Kalimantan. Currently the company has compiled a pit design with SR 1: 22 parameters which are assisted by a consultant PT. Runge Indonesia, the rest is the selling price of coal which is not yet in line with current coal prices. The ultimate pit design alternative is needed in accordance with the  economic prices so that alternative alternatives in some SR scenarios are 15, 17 and 20. Based on the geotechnical recommendations from PT.EBH, the planned single slope geometry is a 10 meter level height, 650  slope for sidewall and highwall and 300  slope for lowwall. The width of the slope is 5 meters with an overall slope of 450. The measured results of the calculation are 1.949.132,91 tons of coal, in the SR 15 pit area 9.92 Ha obtained reserves of 84.075, 13 tons of coal and overburden volume 1.270,539,44 Bcm, on SR 17 the pit area was 15,04 Ha and mine reserves were 138.966,26 tons and overburden volume was 2.387.242,30 Bcm, on SR 20 the pit area was 24,87 Ha, and mine reserves were 291.314,81 tons and overburden volume 5.867.208,26 Bcm.Keywords: Pit Limit, Slope geometry, reserves, Stripping Ratio, Slope